Beyond the Numbers: How Institutional Ownership and Capital Structure Shape Firm Value - Gita Christy; Bryan Wilson Hamonangan Hutabarat (Journal of Accounting and Auditing, 2026)
Purpose – This study aims to analyze the relationship between capital structure, institutional ownership, and profitability on firm value in financial sector companies in Indonesia. Design/methodology/approach – This study uses secondary data from the annual reports of financial sector companies listed on the Indonesian Stock Exchanged (IDX) for the period 2022-2024. Through purposive sampling technique, a sample of 70 companies was obtained with a total of 210 observations. Data analysis was carried out using a panel data regression model using EViews9 software, where the Random Effect Model (REM) was selected as the best model based on the results of the Chow, Hausman, and Lagrange Multiplier tests. Findings – These results of the study shows that Capital Structure has a positive and significant effect on Firm Value. In contrast, Institutional Ownership and Profitability do not have a significant influence on Firm Value in the financial sector during the observation period. This indicates that investors in the financial sector place more value on the management of funding structures compared to the proportion of institutional ownership or short-term profit levels. Research limitations/implications – Companies in the financial swctor are advised to optimize the composition of debt and equity to increase investor confidence. For investors, these results provide insight that the value of companies in the financial sector is influenced by funding stability, so investment strategies need to consider fundamental aspects of capital structure in addition to other macroeconomic factors. JEL : G21, G30, G32, M41